Review of Foreign Historiography Concerning the Problems of the Shadow Economy Expansion in Ukraine - Nekludov, Y. (Вісник Черкаського університету. Серія: Історичні науки, 2018)
The article analyzes foreign researchers’ views on the problems of shadow sector expansion in the Ukrainian economy as well as in the world economy on the whole. A wide conceptual framework of the phenomenon has been analyzed, the concept of shadow economy has been specified, and the key components of this economy have been distinguished. It has been found out that the main reason for superfast rates at which the economic system of the young Ukrainian state became shadow was the intensification of negative tendencies inherited from the Soviet past and developed under market conditions. The most important factors in that period were as follows: the discrepancy between the current legislature and realities of the economic life, excessive control of the state government and local self-government realized through their intrusion into the economic activity. There were also serious conflicts and problems in financial and credit institutions, which resulted in high inflation rates, national currency devaluation, misbalance of state budget and payments that were additional impulses making the national economy even more shadow. Along with negative outcomes, some positive consequences of the shadow Ukrainian economy in that period have been found out. It has been proved that the shadow economy played a role of a certain shock absorber which in the period of transformation processes created additional jobs and encouraged the availability of new goods at low prices. It was that positive factor which encouraged the emergence of the middle class and helped the poorest strata of the society to survive under unstable political, legal, economic, and social conditions.